2020
DOI: 10.1080/17441692.2020.1808039
|View full text |Cite
|
Sign up to set email alerts
|

‘She is like my mother’: Community-based care of drug-resistant tuberculosis in rural Eswatini

Abstract: Patients with drug-resistant tuberculosis (DR-TB) have received community-based care in Eswatini since 2009. Trained and compensated community treatment supporters (CTSs) provide directly observed therapy (DOT), injectables and psychological support. We examined the acceptability of this model of care among DR-TB patients, including the perspective of family members of DR-TB patients and their CTSs in relation to the patient's experience of care and quality of life. This qualitative research was conducted in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Studies in Uganda and Eswatini found that home-based care allowed patients and caregivers more time to seek part-time work, care for children and tend livestock. 34,37 In this cohort, many patients had children to care for and several had difficulties initiating treatment or collecting medication due to employment commitments. This highlights the need for flexibility around hospital admission and daily or monthly dispensing of medication.…”
Section: Public Health Actionmentioning
confidence: 99%
“…Studies in Uganda and Eswatini found that home-based care allowed patients and caregivers more time to seek part-time work, care for children and tend livestock. 34,37 In this cohort, many patients had children to care for and several had difficulties initiating treatment or collecting medication due to employment commitments. This highlights the need for flexibility around hospital admission and daily or monthly dispensing of medication.…”
Section: Public Health Actionmentioning
confidence: 99%
“…Evidence from 13 studies contributed to the quantitative narrative synthesis and meta-analyses ( Table 1 ): four RCTs 21 , 22 , 23 , 24 ; one quasi-randomised trial 25 ; eight non-randomised studies, including five cohort study designs, 26 , 27 , 28 , 29 , 30 two before-and-after study designs 31 , 32 and one mixed methods study. 33 Evidence from 10 qualitative studies 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 and one mixed methods study 33 contributed to the thematic synthesis ( Table 2 ). Three quantitative studies 24 , 30 , 31 have ‘sibling’ qualitative studies 35 , 36 , 39 pertaining to the same intervention; these are counted as one ‘study’ in the narrative description of study characteristics, but both are cited in the text.…”
Section: Resultsmentioning
confidence: 99%
“…Family meetings and support forums. Integrated care Referrals to social workers, substance use centres or short-term inpatient care DOT Clinic-based DOT or SAT by community healthcare worker SSIs and FGD conducted during TB care, 4 years after initiation of intervention Thematic network approach Moderate Walker 2018 38 Nepal To explore the feasibility and acceptability of the different components of a psychological-based support intervention People with MDR-TB (n = 5) MDR-TB healthcare workers at two urban MDR-TB outpatient clinics (n = 2) N = 7 Psychological-based support Health education: materials provided at the start of care to the person with TB and family members Counselling: for people with depression (following a monthly screening), 8 sessions or until depression score reduced below a threshold and additional peer-support group counselling DOT Not reported in study (assumed provided under Nepal's National TB Control Programme as standard of care) SSIs conducted at month 9 and final month of intervention during TB care; reflective diaries and field visit reports Thematic framework analysis Moderate Interventions providing psychosocial support (material and psychological-based support) Burtscher 2020 41 Eswatini To explore the effectiveness, feasibility and acceptability of the different components of a psychosocial support intervention within a community-based model of care People with DR-TB (n = 9) Community treatment supporters (n = 11) and family members of people with DR-TB (n = 9) N = 29 Material support Financial and nutritional: travel allowances and food packages Psychological-based support Counselling: home-based with trained community treatment supporter and community TB nurse DOT Home-based DOT by trained community treatment supporter SSIs, paired interviews (with family members in patients' homes) and FGDs during TB care Thematic analysis Low Charyeva 2019 39 Sibling of 30 Ukraine To explore which components of a psychosocial support intervention worked People with TB...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations